Oil seeps detection and mapping by SAR imagery in the Adriatic Sea - Ivanov, Andrei, oceanolog (Array, 2020)
This study provides a new perspective on the hydrocarbon seeps in the Adriatic Sea, supporting both the environmental issues and eventual oil and gas exploration. Remote sensing techniques, particularly synthetic aperture radar (SAR) images are used to detect oil slicks on the sea surface. In such a way two groups of oil slicks have been detected in the Northern and Central Adriatic Sea on the SAR images acquired by the European Sentinel-1A and Sentinel-1B satellites in 2017-2018. Analysis of SAR images together with bathymetry, geological and geophysical data in geographic information system (GIS) have shown that these oil slicks, visible on the sea surface have natural origin, i.e. are seepage phenomena, associated to existing marine hydrocarbon systems. These oil slicks were concentrated over the shallow shelf, and repeatedly or episodically occur in the areas of interest, and are related to local oil-and-gas bearing sediments. Findings of the seeps and seep candidates that passed unnoticed from public attention indicate the effectiveness of the approach used. Finally, it is concluded that the frequent SAR imagery is an excellent tool for monitoring of seepage phenomena, and the results indicate that the use of remote sensing methods can be considered as a good approach to support oil and gas exploration in the Adriatic Basin.